(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
The lionfih (Pterois volitans) has established in the Colombian Caribbean coast. Its presence was reported for the fist time in continental Colombia in 2009, but its abundance has increased signifiantly by the end of 2009 and 2010, being now common to fid it in the entire Colombian Caribbean. The present study evaluates the diet components of the lionfih in Santa Marta and Tayrona National Park. Five teleost families (Apogonidae, Gobiidae, Serranidae, Clupeidae, and Pomacentridae) and some crustaceans were identifid as components of the diet of the lionfih. Some of these organisms belong to families of ecological and economic importance, which can have impacts on populations of local fih as has happened in other latitudes. Consequently, this species should be controlled and managed in the area to avoid further loss of diversity and abundance of ecological and commercially important fih species in Colombia.